International advances in adoption research for practice - Wrobel, Gretchen Miller; Neil, Elsbeth Catherine; International Conference on Adoption Research 2006 : Norwich, England) (Chichester : Wiley-Blackwell, 2009)
"International Advances in Adoption Research for Practice brings together the cutting-edge research from the worldwide community of leading adoption researchers. Among the issues covered are international and domestic adoption, openness, adoption from the perspective of the birth family, the child and the adopters, and adoption of children with special needs and those from deprived backgrounds. Featuring authors from five different countries, this book provides a truly international and interdisciplinary view on adoption, and is designed to be relevant and accessible to a wide audience, especially practitioners working in adoption."--Jacket
Front Matter -- Adoption in Context. Nature, Nurture and Narratives / David Howe -- How Tight Was the Seal? A Reappraisal of Adoption Records in the United States, England and New Zealand, 1851-1955 / E Wayne Carp -- From Bucharest to Beijing: Changes in Countries Sending Children for International Adoption 1990 to 2006 / Peter Selman -- The Ecology of Adoption / Jesus Palacios -- Research Perspectives. Children from Care can be Adopted / Ruth G McRoy, Courtney J Lynch, Amy Chanmugam, Elissa Madden, Susan Ayers-Lopez -- Understanding Links Between Birth Parents and the Child They Have Placed for Adoption: Clues for Assisting Adopting Families and for Reducing Genetic Risk? / David Reiss, Leslie D Leve, Amy L Whitesel -- Effects of Profound Early Institutional Deprivation: An Overview of Findings from a UK Longitudinal Study of Romanian Adoptees / Michael Rutter, Celia Beckett, Jenny Castle, Emma Colvert, Jana Kreppner, Mitul Mehta, Suzanne Stevens, Edmund Sonuga-Barke -- International Adoption Comes of Age: Development of International Adoptees from a Longitudinal and Meta-Analytical Perspective / Femmie Juffer, Marinus H van IJzendoorn -- Attachment Representations and Adoption Outcome: On the Use of Narrative Assessments to Track the Adaptation of Previously Maltreated Children in Their New Families / Miriam Steele, Jill Hodges, Jeanne Kaniuk, Howard Steele, Kay Asquith, Saul Hillman -- Adopted Adolescents: Who and What Are They Curious About? / Gretchen Miller Wrobel, Kristin Dillon -- Emerging Voices : Reflections on Adoption from the Birth Mother's Perspective / Ruth Kelly -- The Corresponding Experiences of Adoptive Parents and Birth Relatives in Open Adoptions / Elsbeth Neil -- Emotional Distance Regulation over the Life Course in Adoptive Kinship Networks / Harold D Grotevant -- Connecting Research to Practice / Gretchen Miller Wrobel, Elsbeth Neil -- Index.
Includes bibliographical references and index.
Title page from PDF; (John Wiley; viewed on Dec. 20, 2012).
English.
John Wiley and Sons
Keywords: Intercountry adoption -- Congresses; Adoption internationale; Intercountry adoption; Adoption; Adoption; Research; Internationell adoption; Conference papers and proceedings; Congresses (form)